The Effect of Ankle, Knee and Hip Isokinetic Fatigue on Shock Absorption and Rate of Loading during Pair-leg Landing - Hamideh Khodaveisi; Ameneh Hosseinzadeh (Islamic Azad University, Hamedan Branch, 2016)
Objective: This study aims at investigating the effects of ankle, knee, and hip ISO fatigue on shock absorption and rate of loading during paired-leg landing. Methods: Fifteen female students with an average age of 19.67± 0.62 years, weight of 54.60 ± 9.44 kg, and height of 163.30 ± 5.54 cm were selected randomly as subjects in this study. First, the participants were tested by jumping from a box with the height of 30cm, to land on a force plate. Then, the Isokinetic fatigue protocol of the ankles, knees, and hips muscles’ was implemented for everyone by an Isokinetic System, and related information was recorded. The second test of paired- leg landing with fatigue muscles, was carried out on a force plate immediately. For statistical analysis, SPSS version 18 was used and, Dependent samples T-test, at the significance level of P < 0.05, was used.          Results: the results of the dependent samples T- test results showed no significant difference in comparing the rate of load throughout landing before and after fatigue in the joints of the lower extremities. Conclusion: Findings of this study indicate that the fatigue protocol using Isokinetic devices with uniform speed, increases muscle strength due to generating stress at all the joints, thereby, compensating the active and passive joints for shock absorption, and load distribution on the lower extremities.